2012
DOI: 10.1603/en10313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Temperature and Moisture on Survival of Eggs and First-Instar Larvae of Delia radicum

Abstract: Edaphic factors such as soil temperature and moisture influence soil-dwelling insects, whose most vulnerable stages typically are eggs and young larvae. In this study, the survival of eggs and first-instar larvae of the cabbage maggot, Delia radicum L., was measured under laboratory conditions after exposure to a range of soil temperatures and moistures. When eggs were exposed to constant temperature (20-29°C) and humidity (5-200% [wt:wt]), temperature had no significant effect on survival, whereas humidity <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Egg mortality was also relatively constant (Ϸ11%) with temperature. Different results were obtained for larvae survival, which tends to increase with an increase in soil temperature and moisture (Lepage et al 2012). Immature stages that hatched from eggs of both the early and late-emerging genotypes had the same probability of survival.…”
Section: Discussionmentioning
confidence: 84%
“…Egg mortality was also relatively constant (Ϸ11%) with temperature. Different results were obtained for larvae survival, which tends to increase with an increase in soil temperature and moisture (Lepage et al 2012). Immature stages that hatched from eggs of both the early and late-emerging genotypes had the same probability of survival.…”
Section: Discussionmentioning
confidence: 84%
“…; Lepage et al . ). Our results implied that there were variations in the relationships to climate among different species of Diptera.…”
Section: Resultsmentioning
confidence: 97%
“…Bligaard [ 31 ] reported that the percentage of mortality of eggs and larvae is very high (between 47% and 61%). Eggs of D. radicum are resistant to low soil moisture and high temperature conditions, while larval survival tends to increase with an increase in soil temperature up to 33 °C and in the and moisture [ 32 ]. Climatic conditions during the period of egg laying and larval development (April and May) in 2011 were similar to those observed in the other three years, which supports the idea that the absence of wilting symptoms was due to other factors.…”
Section: Resultsmentioning
confidence: 99%
“…Climatic conditions during the period of egg laying and larval development (April and May) in 2011 were similar to those observed in the other three years, which supports the idea that the absence of wilting symptoms was due to other factors. In May of 2011 the amount of precipitation was the highest among all experimental years, and this may have influenced larval survival [ 32 ]. Several authors [ 8 , 33 , 34 ] have suggested that some of the 60–100 species of carabid and staphylinid beetles found commonly in cultivated soils are important predators or parasitoids of the cabbage maggot and that their activity is related to crop rotation and cultivation practices.…”
Section: Resultsmentioning
confidence: 99%